2015
DOI: 10.18819/ijavs.2015.1542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin – Mineral Supplement on the Immune Response of Broilers to Newcastle Disease Vaccination

Abstract: To study effects of vitamins-minerals (VMS) supplementation on immune response of chicks to Newcastle disease vaccination (NDV-LaSota), one hundred broiler chicks were assigned to 4 treatment groups of 25 each. One group was given VMS before the vaccination. Another group was given the supplementation after the vaccination. A third group was given the VMS before and after the vaccination while the fourth group served as vaccinated control. Administration of VMS was in each case, through drinking water. Five ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…To optimize the growth potential of modern broilers in the commercial farms, supplementing the commercial broiler feeds with growth promoters [ 2 ], probiotics [ 3 ], minerals and vitamins [ 4 - 6 ], green foliage/leaf meals [ 7 ], exogenous enzymes [ 8 ], or essential amino acids [ 9 ] has been conducted. With regard to probiotics, vitamins, and minerals, these components have been known to exert an immune-enhancing effect on poultry [ 10 , 11 ]. Hence, supplementation of commercial broiler feeds with probiotics in combination with vitamins and minerals seemed to be beneficial not only for better growth but also for health of broiler chicks on the commercial farms.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the growth potential of modern broilers in the commercial farms, supplementing the commercial broiler feeds with growth promoters [ 2 ], probiotics [ 3 ], minerals and vitamins [ 4 - 6 ], green foliage/leaf meals [ 7 ], exogenous enzymes [ 8 ], or essential amino acids [ 9 ] has been conducted. With regard to probiotics, vitamins, and minerals, these components have been known to exert an immune-enhancing effect on poultry [ 10 , 11 ]. Hence, supplementation of commercial broiler feeds with probiotics in combination with vitamins and minerals seemed to be beneficial not only for better growth but also for health of broiler chicks on the commercial farms.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of vitamins (A, D3, E, B-group water-soluble vitamins), minerals (selenium) and amino acids have a great role in immune modulation and stimulating humoral and cellular immunity and also most effective mechanism to tackle vaccine [18,39].…”
Section: Administration Of Vitamin and Mineralmentioning
confidence: 99%
“…it is better to vaccinate the birds prior to the incidence of the disease so that the birds develop the required amount of antibody titration. For instance, vaccination against infectious bronchitis and avian influenza should be given before winter period since the outbreak of diseases are commonly occurs in birds during winter [18,21]. Besides, biosecurity is the most important and crucial component of any poultry outbreak prevention and control strategy and should be maintained at a high level to complement vaccine use.…”
Section: Correct Vaccination Schedule and Strick Biosecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally,Sanda (2019) reported a significant increase in antibody titer to Newcastle Disease vaccine in chickens supplemented with vitamin-mineral mix compared with the control, and the group received the supplement only without a vaccine Redmond et al (2010) andEl Nahas et al (2019). suggested that different genetic backgrounds of chicken affect their response to immune enhancing.The results of subchronic Salmonella infection three-week postchallenge revealed no change in IL-1β gene expression in both high and low immune response birds in the Fayoumi breed Beal et al (2005).…”
mentioning
confidence: 99%